KONSTRUKSI STRATEGI PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES SEBAGAI UPAYA PEMECAHAN MASALAH BELAJAR - Chusnul Muali (Nurul Jadid University, 2016)
Most people still think that the value of an individual’s intelligence is al- ways measured by the ability in solving mathematical problems aside the fact that there is a plurality of the human intelligence since he was born. The learning strategy plays an important role in accommodating the ful- fillment of it to reach almost all intelligence possessed by the students. In the process, the learning should have a pattern and management elements of grammar, sequence, logic, order and sequence, problem solving, map- ping, individual experience, to social relationships through interaction and discussion. To meet these needs, the selection of learning strategies based intelligence compound is apt to be a critical success factor learning process.